QUALITY AND SUSTAINABILITY OF PRODUCTION OF YOHURT FROM SOYABEANS, TIGER NUT, AND DATE (FUDMA JOURNAL OF SCIENCES, 2023)
Yogurt, is also known as yoghurt, is one of the most known popularly fermented dairy products in the world, with a wide range of health benefits in addition to basic nutrition and was believed to have therapeutic powers and give long life to those who consumed it. This study aimed to evaluating the quality and suitability of production of yoghurt using blended tiger nut milk, soybeans milk and date milk. Proximate and microbial analysis was used to determine nutrient composition and quality of the produced yogurt. The study shows the mean scores ranges of proximate composition (moisture, ash, protein, fat, crude fibre and carbohydrate) of the formulated yoghurt: 75.83±1.44, 70.16±0.28, 81.00±1.73, 80.00±0.00, 0.61±0.02 – 0.76±0.02, 5.40±0.17 – 7.43±0.05, 5.33±0.03 – 6.40±0.00, 0.04±0.00 – 0.12±0.00. and for carbohydrate content, the mean score ranged from 4.27 ±1.81 – 17.16 ±0.54. The bacterial total plate count of the sample ranged from 1.6x102 – 9.7x103 cfu/ml. Sample A (1.3x102) had lowest growth while sample D (9.7x103) had highest growth. For appearance, the mean score ranged from 6.00±2.22 – 8.25±0.63, also for aroma, the mean score ranged from 6.45±2.41 – 7.50±0.94 and for overall acceptability, the mean score ranged from 6.40±2.37 – 8.00±0.64. This study revealed that soy milk, tiger nut milk and date palm juice produced can be effectively used for acceptable yogurt formulations..
Keywords: proximate; microbial; quality; sustainability; acceptability; sensory